Ontology Application for the Hajj - Dinfir, Nawal Masoud S.M. (2009)
In this our dynamic world, knowledge is related to data and information that already exist, and knowledge management can be shared and interlinked. In a broader scope, it can be used to structure ontology. The use of ontology on knowledge helps users to understand the structure easier. The important matter in ontology is represented by showing the relations among classes in domain. When the relation is already identified, then the structure of ontolopy for the knowledge domain (i.e. Al-Hajj) can be modelled. Protege is used in this work to model the structure of ontology. This structure of ontology will assists in sharing knowledge about Al-Hajj.